Aktualʹnye problemy sozdaniâ "Frazeologičeskogo slovarâ russkih govorov" - Arefʹeva, Natalʹâ (Słowiańska frazeologia gwarowa II, 2020)
ACTUAL PROBLEMS OF CREATING RUSS IAN DIALECTS’PHRASEOLOGICAL DICTIONARY OF ODESSA REGIONIn this article the difficulties and problems faced by the author of this study in the process of creating the phraseological dictionary of Russian dialects of Odessa region are delighted. It is noted that referring to the data of general and regional dictionaries in the process of selecting linguistic facts, determining their explicit and implicit content made it possible to correct (and in many cases fixation, subsequent semantization and further grammatical-stylistic and ethnocultural description that take into account inter-dialect and inter-lingual interference) the heterogeneous and diverse phraseological material presented in the projected dictionary. In the process of verifying and analyzing dialect phraseological units, the author uses such types of correction as semantic, lexical, grammatical, stylistic, phonetic ones, accent correction or their combination. Each of these types is examined in detail. The author comes to the conclusion that the process of linguistic processing of extensive linguistic material is multidimensional and multifaceted, and phraseological identification and codification include a number of stages and procedures, the ultimate goal of which is a system complex characteristic of the revealed dialect phraseological unit.